Divestiture and Share Price - Boudreaux, Kenneth J. (Journal of Financial and Quantitative Analysis, 1975)
As an alteration of the firm's productive asset portfolio, divestiture is the mirror-image of asset acquisition or merger. Yet, though significant efforts have been expended by researchers into the implications of acquisition and merger, the literature of finance is all but silent on the subject of divestiture.